PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA SEKTOR PROPERTY & REAL ESTATE - Sagita Charolina Sihombing; Venny Piuty; Dina Agnesia Sihombing (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2025)
This research aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity Ratio (ROE) and Firm Size on Corporate Social Responsibility in property and real estate company sector listed on the Indonesian Stock Exchange for the period 2019 - 2023. This research uses secondary data. The sampling technique in this research used purposive sampling. The number of samples obtained was 35 companies. The analytical method for this research uses descriptive and linear regression analysis using the IBM SPSS (Software Statistical Package for Social Science) program. From this research, it can be concluded that Current Ratio, Debt to Equity Ratio and Firm Size have a significant influence on Corporate Social Responsibility while Return on Equity Ratio (ROE) has no effect on corporate Social Responsibility. Penelitian ini bertujuan untuk mengetahui pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity Ratio (ROE) dan Firm Size terhadap Corporate Social Responsibility pada perusahaan sektor properti dan real estate yang terdaftar di Bursa Efek Indonesia periode 2019 - 2023. Penelitian ini menggunakan data sekunder. Teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling. Jumlah sampel yang diperoleh sebanyak 35 perusahaan. Metode analisis penelitian ini menggunakan analisis deskriptif dan regresi linier dengan menggunakan program IBM SPSS (Software Statistical Package for Social Science). Dari penelitian ini dapat disimpulkan bahwa Current Ratio, Debt to Equity Ratio dan Firm Size berpengaruh signifikan terhadap Corporate Social Responsibility sedangkan Return on Equity Ratio (ROE) tidak berpengaruh terhadap Corporate Social Responsibility.